A letter from Giovanni Rosini on the plagiarism of Paolo Mascagni’s anatomical tables - Natale, Gianfranco; Gremigni Francini, Lorenzo; Armocida, Emanuele (Medicina Historica, 2026)
The primary sources are precious testimony for the most objective possible reconstruction of historical facts. Therefore, they play a fundamental role in clarifying disputes and controversies. Debated aspects are quite frequent in the scientific field, as far as the attribution or priority of discoveries and publications is concerned. An important dispute arose in the first half of the 19th century, regarding the intriguing question of the plagiarism of the posthumous work Anatomia Universa of the famous Tuscan anatomist Paolo Mascagni (1755-1815) by his dissector Francesco Antommarchi (1780-1838). A contribution to the clarification of this controversy is provided by the discovery of an unpublished epistolary document which is now transcribed and commented in this article. It is a letter written in Pisa on 14 June 1823 by Giovanni Rosini (1776-1855), a friend and colleague of Mascagni, and addressed to the French bookseller and bibliographer Antoine-Augustin Renouard (1765-1853). Rosini was one of the three curators of the posthumous work, together with Andrea Vaccà-Berlinghieri (1772-1826) and Giacomo Barzellotti (1768-1839), and he soon worked to defend Mascagni from the plagiarism of Antommarchi. This epistolary document demonstrates and confirms that Rosini tried to denounce and hinder the incorrect behavior of Mascagni’s pupil.